2015
DOI: 10.1016/j.yebeh.2015.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Deep hypothermia for the treatment of refractory status epilepticus

Abstract: In a rat model of status epilepticus (SE) induced by lithium and pilocarpine and refractory to midazolam, deep hypothermia (20°C for 30 min.) reduced EEG power over 50-fold, stopped SE within 12 minutes, and reduced EEG spikes by 87%. Hypothermia deserves further investigation as a treatment of last resort for refractory SE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 64 publications
1
19
0
1
Order By: Relevance
“…EEG power in normothermic animals decreased from pretreatment SE, probably in part due to midazolam, but remained significantly above baseline for 4.1 ± 1.1 h (mean ± SEM; n = 9) after midazolam injection, indicating continuation of SE. In hypothermic animals, cooling brought power down to baseline level in 23.8 ± 3.9 min (mean ± SEM; n = 5) and significantly lowered EEG power compared to normothermia at 30 min and beyond as described in a preliminary report . In these animals, EEG power decreased below prepilocarpine baseline, and remained close to baseline values for the remaining of the 24 h, suggesting that SE had been terminated and did not return.…”
Section: Resultsmentioning
confidence: 51%
“…EEG power in normothermic animals decreased from pretreatment SE, probably in part due to midazolam, but remained significantly above baseline for 4.1 ± 1.1 h (mean ± SEM; n = 9) after midazolam injection, indicating continuation of SE. In hypothermic animals, cooling brought power down to baseline level in 23.8 ± 3.9 min (mean ± SEM; n = 5) and significantly lowered EEG power compared to normothermia at 30 min and beyond as described in a preliminary report . In these animals, EEG power decreased below prepilocarpine baseline, and remained close to baseline values for the remaining of the 24 h, suggesting that SE had been terminated and did not return.…”
Section: Resultsmentioning
confidence: 51%
“…Therefore, we used both C57BL/6J mice and Gfap‐Gfp transgenic mice on a C57BL/6NCr background to investigate the appropriate experimental conditions. A literature search indicated that systemic pilocarpine administration induces hypothermia in mice (Friedman & Jaffe, ; Glick & Marsanico, ), and that hypothermia prevents the development of epileptic seizures (Kowski, Kanaan, Schmitt, & Holtkamp, ; Niquet, Baldwin, Gezalian, & Wasterlain, ). We also found that although in some studies on the pilocarpine model, mice were kept in an incubator set at 30–32°C (Cho et al, ; Walter, Murphy, Pun, Spieles‐engemann, & Danzer, ), they did not clearly mention the effect of the incubator on mouse body temperature, SE induction, survival, and mortality.…”
Section: Resultsmentioning
confidence: 99%
“…To overcome these problems, we improved the procedure for inducing epileptic seizures in C57BL/6J and C57BL/6NCr mice, by use of a heated platform. This improved procedure is based on the following two facts: 1) the systemic administration of pilocarpine to mice results in a profound decrease in body temperature (Friedman & Jaffe, ), and 2) hypothermia in mice has an anticonvulsant effect (Kowski et al, ; Niquet et al, ). In fact, we found a sharp drop in body temperature after pilocarpine injection in mice, as well as a low rate of incidence of seizures.…”
Section: Discussionmentioning
confidence: 99%
“…Animal studies have demonstrated that therapeutic hypothermia has neuroprotective and antiepileptic properties. In a rat model of SE, deep hypothermia (20 °C) of 30 min duration terminated RSE within 12 min of initiation of hypothermia and eliminated SE-induced neuronal injury in most animals [79]. A case series of five children with RSE who were treated with mild hypothermia (32-35 °C) demonstrated reduction in seizure burden during and after hypothermia treatment without relapse after hypothermia [80].…”
Section: Therapeutic Hypothermia and Other Non-pharmacologic Therapiesmentioning
confidence: 99%